Experimental data and thermodynamics modeling (PC-SAFT EoS) of the {CO2 + chloroform + PHBV} system at high pressures - Favareto, Rogerio; de Araujo, Paulo Cardozo Carvalho; Bezerra, Isaac Dias; Zanette, Andreia Fátima [UNESP]; Arce, Pedro Felipe; Ferreira-Pinto, Leandro [UNESP]; Cardozo-Filho, Lucio [UNESP] (Elsevier, 2021)
Herein, the influence of HV (hydroxyvalerate) addition (8.0 and 8.7 wt% HV) on the PHBV (poly(3-hydroxybutyrate-co-3-hydroxyvalerate)) composition from the perspective of phase equilibrium in high-pressure {(CO2 (1) + chloroform (2) + [PHBV - 8.0 wt%] (3) and (CO2 (1) + chloroform (2) + [PHBV - 8.7 wt%] (3)} systems was examined using the static synthetic method with a visual variable-volume view cell at temperatures ranging from 303.15 to 333.15 K, pressures approximately 10 MPa, and different concentrations of PHBV (HV = 8.0 and 8.7 wt%) in chloroform (0.01 and 0.02 g.cm−3). Transitions of the solid-vapor-liquid (SVL) were observed. The experimentally determined phase transitions were successfully modeled using the PC-SAFT equation of state.
Keywords: Chloroform; CO2; Phase equilibrium; PHBV; Supercritical